MENINGKATKAN KETERAMPILAN PROSES SAINS DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DAN TAKE AND GIVE PADA MUATAN IPA KELAS 5 SDN TATAH BELAYUNG BARU - Farras Nur Rania; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this study is the low science process skills and WASAKA character (discipline character and hard work character) of students in science subjects. The purpose of this study is to describe teacher activities, analyze science process skills, student activities, WASAKA characters and student learning outcomes. This study uses 2 approaches, namely quantitative and qualitative, with clear Classroom Action Research (CAR) which is carried out in four meetings. The subjects of the study here are grade 5 students of the even semester of SDN Tatah Belayung Baru. This study uses qualitative and quantitative data. The results of this study indicate that teacher activities are carried out to reach a value of 97% with a very good category, students' science process skills reach a percentage of 100% with a very skilled category, student activities are carried out to reach a percentage of 93% with a very active category, students' cognitive learning outcomes reach a percentage of 100% with a complete category, affective learning outcomes reach 100% with a cultural category and psychomotor learning outcomes reach 100% with a very good category. Based on this research, it can be concluded that using the Problem Based Learning, Take and Give model can improve the Science Process Skills and WASAKA character of grade 5 students in science content.